Decomposition of oat straw and release of macronutrients in different managements - Francisco Egewarth, Jonas; Tiago Piano, Jeferson; Augusto Rocha de Moraes Rego, Carlos; Mattei, Eloisa; Aline Egewarth, Vanessa; Sérgio Rabello de Oliveira, Paulo (Scientia Agraria Paranaensis, 2021)
The present work was aimed in order to evaluate the decomposition process of remaining straw from oat cultivars submitted to different handling during the cultivation of corn for silage intercropped with Urochloa brizantha cv. MG13 Braúna. We considered nine oat cultivars named as follows: "IAPAR 61 IBIPORÃ" oat hay (61F), "IAPAR 61 IBIPORÃ" pasture (61P), "IAPAR 61 IBIPORÃ" cover crop (61SM), "Embrapa 139 (Fog)" oat hay (139F),"Embrapa 139 (Fog)" pasture (139P)," Embrapa 139 (Fog)" cover crop (139SM), "Emerald IPR 126" oat hay (EF), "Emerald IPR 126" grazed (EP) and "Emerald IPR 126" cover crop (ESM) from which we evaluated the decomposition of the remaining straw using the method of litter bags. The evaluations were carried out at 0, 15, 30, 60, 90 and 108 days after sowing corn for silage intercropped with Brizantha brachiaria cv. MG13 Braúna (Urochloa brizantha). Every oat cultivar had three repetitions arranged in a split-plot design. We took into account the quantity of straw, organic matter, carbon, nitrogen, carbon / nitrogen ratio, phosphorus and potassium. The results we got clarify that oat decomposition rate varied with the meteorological factors and initial mass, so that the greater the initial mass is, the longer the straw permanency and mulch effectiveness on the soil. The time the residual oat straw took to be decomposed depended on meteorological factors both during the cover crop developmental stage and the decomposition period itself. The higher the initial mass, the greater the time and effectiveness of mulching.